Analysis of Integrated Healthcare Centre (Posyandu) Management Information System in Lapai Public Health Centre - ., Yulia; Rahma, Gusni; Prihastita Rizyana, Nurul; Rahmi, Afzahul (KnE Life Sciences, 2021)
Integrated Healthcare Centre (Posyandu) management information systems are used to facilitate the process of recording and reporting Posyandu activities carried out by cadres. The purpose of this study was to analyse the Posyandu information system at Lapai Public Health Centre. This research used a combination of quantitative and qualitative methods. While the independent variables were the knowledge and behaviour of the cadres, the Posyandu information system training, the length of work of the cadres, and monitoring the Public Health Centre, the dependent variable was the Posyandu Information System. The quantitative data analysis was done using a univariate analysis while qualitative data were analysed using the triangulation method. The results showed that 100% of Posyandu data were recorded by cadres using books/papers, 100% data processing was still manual, 77.8% Posyandu data were actively reported by cadres to the Posyandu’s person in charge, 100% of the information was disseminated, 41.7% of cadres had knowledge, 69.4% of cadres had worked for more than five years, 94.4% of cadres had received training, 72.2% of the data were recorded and reported completely, and 83.3% of the data were reported on time. An offline computerized recording system needs to be made so that it is easier to combine all Posyandu data at Public Health Centres. Keywords: analysis, management information system, integrated healthcare centre